Hocam Prof. Dr. Tuncer Gülensoy - Buran, Ahmet (Bengü Yayıncılık, 2022)
Tuncer Gülensoy, yurt içinde; Ankara, Fırat, Erciyes Üniversitelerinde, yurt dışında ise, Amerika’da, Texas Tech; Kırgızistan’da, Manas; Kıbrıs’ta, Girne Amerikan Üniversitelerinde görev yapmıştır. Altayisitik ve Mongolistik’ten Türk dilinin tarihi ve çağdaş lehçelerine, etimolojiden ağızlara, adbiliminden halkbilimine kadar Türkoloji’nin hemen her alanında birçok makale ve kitap yayınlamış, yüksek lisans ve doktora tezleri yaptırmış ve çok sayıda öğrenci yetiştirmiştir. Telif eserlerinin yanında çeşitli çeviri eserler de yayınlayan Tuncer Gülensoy, Türkiye Türkolojisinin en çok öğrenci yetiştiren, en çok yazan ve tanınan hocalarından biridir. 30 Ocak 1939 tarihinde Uşak’ta doğmuş ve 11. 06. 2022 tarihinde Ankara’da vefat etmiştir.

Tuncer Gülensoy, in the country; In Ankara, Fırat, Erciyes Universities, abroad, in the USA, Texas Tech; in Kyrgyzstan, Manas; He worked at Girne American Universities in Cyprus. He has published many articles and books in almost every field of Turcology, from Altaicistic and Mongolistic to historical and contemporary dialects of the Turkish language, from etymology to dialects, from onology to folklore, and has had master's and doctoral theses and trained many students. Tuncer Gülensoy, who has published various translated works besides his copyrighted works, is one of the most well-known and well-known professors of Turkish Turcology who educates the most students. He was born on 30 January 1939 in Uşak and died on 11.06.2022 in Ankara.
My teacher, Prof. Dr. Tuncer Gulensoy
Keywords: Linguistics; Dilbilim